Maintaining the colour, texture and vitamin C of cold-stored pineapples through shrinkwrapping and surface-coating with liquid raraffin - Mohamed, Suhaila; Abdullah Khir, Safiah (Universiti Putra Malaysia Press, 1993)
Low density polyethylene shrinkwrapping significantly reduced weight loss and texture loss in Mauritius pineapples stored at 10°C, 15°C, 20°C and ambient temperatures. Suiface coating with paraffin inhibited internal browning in cold-stored pineapples and helped retain a high vitamin C content in the pineapples during storage. Paraffin coating was most effective at maintaining the colour of fresh pineapples and reducing the acidity. A combination ofparaffin waxing and shrinkwrapping was found to be effective in maintaining all the parameters studied. Control untreated pineapples exhibited high weight loss, texture loss, over ripening, fungal attack and internal browning during cold storage. Weight loss was found to be negatively correlated to ascorbic acid content and pulp texture under most conditions.